Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Step-by-step explanation:
[tex] \large{ \sf \underline{Solution - }}[/tex]
To rationalise :
[tex] \sf \implies\cfrac{3 + 2 \sqrt{5} }{5 - 2 \sqrt{3} } [/tex]
➢ Here the denominator is in the form of (a-b). Rationalising factor of (a-b) is (a+b). So, rationalising factor of (5-2√3) is (5+2√3). We will multiply (5+2√3) with both the numerator and denominator to rationalise the denominator.
Now,
[tex] \sf \implies\cfrac{3 + 2 \sqrt{5} }{5 - 2 \sqrt{3} } \times\cfrac{5+2 \sqrt{3} }{5+2 \sqrt{3} } [/tex]
Combine fractions
[tex]{ \sf \implies\cfrac{(3 + 2 \sqrt{5})(5+2 \sqrt{3} ) }{(5 - 2 \sqrt{3})({5+2 \sqrt{3}) } }}[/tex]
We know that,
[tex]\sf \implies (a + b)(a - b) = a^{2} - b ^{2} [/tex]
So,
[tex] \sf \implies\cfrac{(3 + 2 \sqrt{5})(5+2 \sqrt{3} ) }{(5) ^{2} - (2 \sqrt{3})^{2} }[/tex]
Simplify the denominator,
[tex] \sf \implies\cfrac{(3 + 2 \sqrt{5})(5+2 \sqrt{3} ) }{25 - 12 }[/tex]
[tex] \sf \implies\cfrac{(3 + 2 \sqrt{5})(5+2 \sqrt{3} ) }{13 }[/tex]
Now, simplify the numerator,
[tex] \sf \implies\cfrac{3(5 + 2 \sqrt{3}) + 2 \sqrt{5} (5 + 2 \sqrt{3} ) }{13 }[/tex]
[tex] \sf \implies\cfrac{15 + 6 \sqrt{3} + 10 \sqrt{5} + 4 \sqrt{15} }{13 }[/tex]
Hence,
On rationalising we got,
[tex] \bf \implies\cfrac{15 + 6 \sqrt{3} + 10 \sqrt{5} +4\sqrt{15} }{13 }[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.